A multi agent based energy and fault aware scheme for WSN of hard-to-reach territories. (13th June 2022) - Dwivedi, Rajendra Kumar; Kumar, Rakesh; Buyya, Rajkumar
There are various applications of sensor networks in hard-to-reach territories. Sensor has limited energy. Therefore, several energy efficient methodologies have been devised to minimise the energy consumption. The manuscript discovers and resolves limitations of the existing multiple agent schemes which include energy consumption, fault handling, itinerary planning and positioning of sink. Existing protocols placed sink at centre of sensing area. This job is very difficult in hard-to-reach territories. So, a multi agent based energy and fault aware scheme for hard-to-reach territories (MAHT) has been devised. It provides a method of accumulated impact factor (AIF) for identifying the central node with high energy. Its novel agent migration scheme improves the energy efficiency. Planning the itinerary dynamically results in fault tolerance. Proposed protocol is simulated with Castalia simulator and its performance is evaluated on various metrics demonstrating that MAHT outperforms the existing schemes.